Contextual Approach in Designing Informal School for Children in Tulamben Village, Karangasem Collaboration of Warmadewa Architecture-Journeyman International-Suwandi Foundation - Nugraha, Putu Gede Wahyu Satya; Prabandari, Nyoman Ratih; Wiguna, Made Mas Surya; Mahayani, Ni Komang Indra; Widyantara, Dewa Putu; Saputra, I Kadek Yadnya; Ramadhani, Annastashya (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2023)
Informal school in Tulamben Village, Karangasem by Warmadewa Architecture-Power of Experience-Humanity Projects, The Journeyman International, and Suwandi Foundation use Contextual Approach on the design and build process. This Project aims to help the community in Tulamben provide an informal school with Contextual approach and child friendly design. This approach was applied by using the local material, community support on the building process, open plan layouting, maximizing air circulation and natural lighting, and environment and child friendly. This collaboration focuses on safety and children's spatial needs as users. The results of these activities are Informal School design works and the constructed building with children and environment-friendly approach. The design and construction of an informal school for children in Tulamben Village only pays attention to target users and adjustments to the surrounding environment, and has not considered the wider community aspect yet.